Evaluating the Gains of Using Stories in Medical Education–A Pilot Study Example (Bangladesh Journal of Medical Science, 2022)
Objectives: Medical education develops day by day with the effect of its unique dynamics, excessive information load and changing education approach depending on its professional characteristics.The aim of this study wasto determineeffects on the knowledge and attitude gains of story usage in education.Material and Methods: This is a training intervention study with a twenty-five study group and twenty-five control group students. A 20-question test was applied to the students before and after the study, including the topics of course. In addition, students were asked to provide feedback on the educational practice.Results and Dıscussion: According to the results of this study applied with twenty-five students study and control groups; in addition to theoretical lessons, reading and discussing patient stories covering lesson topics significantly increases students’ academic knowledge (p